1989
DOI: 10.1056/nejm198905183202001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Deletions in Progressive External Ophthalmoplegia and Kearns-Sayre Syndrome

Abstract: We investigated the correlations of deletions of mitochondrial DNA in skeletal muscle with clinical manifestations of mitochondrial myopathies, a group of disorders defined either by biochemical abnormalities of mitochondria or by morphologic changes causing a ragged red appearance of the muscle fibers histochemically. We performed genomic Southern blot analysis of muscle mitochondrial DNA from 123 patients with different mitochondrial myopathies or encephalomyopathies. Deletions were found in the mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
365
2
17

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 914 publications
(397 citation statements)
references
References 19 publications
13
365
2
17
Order By: Relevance
“…Muscle biopsies from patients with KSS or CPEO show ragged-red fibers and cytochrome oxidase-negative fibers [58,59]. Clinical signs vary widely in different syndromes but include muscle weakness, heart block, retinopathy, deafness, diabetes, short stature and dementia [2,60]. We have used microarray in an attempt to link the primary cause of KSS/CPEO/PS with cellular, morphological, and clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle biopsies from patients with KSS or CPEO show ragged-red fibers and cytochrome oxidase-negative fibers [58,59]. Clinical signs vary widely in different syndromes but include muscle weakness, heart block, retinopathy, deafness, diabetes, short stature and dementia [2,60]. We have used microarray in an attempt to link the primary cause of KSS/CPEO/PS with cellular, morphological, and clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA deletions (ΔmtDNA), when present at concentrations of 30% and greater in muscle tissue, can cause three disorders, Kearns-Sayre Syndrome (KSS), Chronic Progressive External Opthalmoplegia (CPEO), and Pearson's Syndrome (PS) [1][2][3]. Clinical signs include muscle weakness, exercise intolerance, droopy eyelids and weakness of ocular muscles (CPEO), plus heart block, pigmentary retinopathy, ataxia, deafness, and dementia (KSS), and sideroblastic anemia (PS).…”
Section: Mitochondrial Deletions Cause Kss Cpeo and Psmentioning
confidence: 99%
“…Larger mtDNA deletions have been associated with more severe disease and earlier disease onset 15, 16, 17, 18, 19. Whereas a highly significant,20 significant,15, 16, 21, 22 weak,18, 23 or no24 correlation has been reported between the percentage of COX‐deficient fibers and the degree of mtDNA heteroplasmy, most studies found no correlation between the biochemical defects and the nature of the deletion (the number of protein‐encoding genes and the complexes affected by the deletion) or deletion size alone 4, 15, 20, 22, 25. Interestingly, a higher proportion of COX‐deficient ragged‐red fibers was found in patients with deletions encompassing the 3 mtDNA‐encoded COX genes,26, 27 whereas an isolated complex I deficiency was reported in patients with smaller mtDNA deletions removing only complex I genes 26…”
mentioning
confidence: 99%
“…Phenotypically, single large‐scale mtDNA deletions are associated with several clinical syndromes including Pearson syndrome,2 Kearns–Sayre syndrome,3 and chronic progressive external ophthalmoplegia (CPEO) 4. A recent prospective study noted ptosis, ophthalmoplegia, muscle weakness, exercise intolerance, and hearing loss as the most common symptoms present at onset 5…”
mentioning
confidence: 99%
“…Similarly, the abundance of the mutation in accessible tissues (blood, skin fibroblasts, hair roots, urinary tract cells) generally correlates reasonably well with clinical severity in oligosymptomatic maternal relatives of patients with MELAS or MERRF. An apparent exception to this rule is KSS, in that "partial cases" with some but not all the canonical diagnostic features seem to be very rare: we had found only 4 such "probable" cases in our series of 54 patients with PEO and single mtDNA deletions (Moraes et al, 1989) and we have seen very few since then.…”
Section: Defects Of Mitochondrial Genesmentioning
confidence: 67%